2022
DOI: 10.1080/21655979.2022.2044251
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC01426 promotes the progression of lung adenocarcinoma via regulating miRNA-125a-5p/ casein kinase 2 alpha 1 axis

Abstract: Although long noncoding RNAs (lncRNAs) in lung adenocarcinoma (LUAD) have been increasingly studied, LINC01426 has not been fully investigated in LUAD. The GEPIA database revealed that LINC01426 was upregulated in LUAD tissues. In our study, we further verified the significantly high expression of LINC01426 in LUAD tissues and cell lines. We also analyzed the LINC01426 expression level and LUAD clinical features and found that high LINC01426 expression was associated with tumor diameter; tumor, node, and metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It is indicated that LINC01426 may serve as a tumor biomarker. Several previous reports demonstrated the functions of LINC01426 in lung cancer [ 14 17 ]. However, the underlying molecular mechanism of LINC01426 in lung adenocarcinoma still remains to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that LINC01426 may serve as a tumor biomarker. Several previous reports demonstrated the functions of LINC01426 in lung cancer [ 14 17 ]. However, the underlying molecular mechanism of LINC01426 in lung adenocarcinoma still remains to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in our constructed 3-ferroptosis-related lncRNA signature, LINC01426 is an oncogene that has been validated by many cancer researchers. LINC01426 promotes the development of lung cancer ( Dai et al, 2020 ; Han et al, 2020 ; Liu et al, 2021 ; Zhu et al, 2022 ), clear cell renal cell carcinoma ( Jiang et al, 2021 ), and osteosarcoma ( Zhang et al, 2021 ). Furthermore, the role of LINC01426 in glioma has also received increasing attention, including sponging miR-345-3p and upregulating VAMP8 to promote glioblastoma ( Cao et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al. ( 56 ) found that LINC01426 promotes the progression of lung adenocarcinoma via regulating miRNA-125a-5p/casein kinase 2 alpha 1 axis. Tang et al.…”
Section: The Regulation Of Signaling Pathway That Lncrna Participated...mentioning
confidence: 99%